2009
DOI: 10.1038/npre.2009.3239.1
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids composition of some freshwater fish

Abstract: The aims of this paper were to investigate the component fatty acids of some freshwater fish species by comparing the levels of essential fatty acids present. The FAME were determined by GC-MS and were identified using retention time locked methods and retention time databases. The fatty acids profiles include minor amounts of odd-number, branched-chain, and even-number fatty acids as well as saturated components, the MUFA and PUFA. The major SFA were C14:0 and C16:0. The C18:1 was the prominent MUFA. The domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The level of oleic acid in the American freshwater channel catfish flesh was also high compared to sardine and sea mullet (Ackman, 1994). Although level of oleic acid was lower than the level found in some freshwater fish (Khoddami et al, 2009), it was almost similar to the level reported in other freshwater fish (Zenebe et al, 1998;Bieniarz et al, 2000;Saba et al, 2000;Ackman et al, 2002;Ben Smida et al, 2009;Sharma et al, 2009;Ugoala et al, 2009;Elagba and Al-Sabahi, 2011). The variation of n-3 PUFA detected in the different studied organs of P. annectens ( Figure 6) was to some extent within the range found in other fish species (Suriah et al, 1995).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The level of oleic acid in the American freshwater channel catfish flesh was also high compared to sardine and sea mullet (Ackman, 1994). Although level of oleic acid was lower than the level found in some freshwater fish (Khoddami et al, 2009), it was almost similar to the level reported in other freshwater fish (Zenebe et al, 1998;Bieniarz et al, 2000;Saba et al, 2000;Ackman et al, 2002;Ben Smida et al, 2009;Sharma et al, 2009;Ugoala et al, 2009;Elagba and Al-Sabahi, 2011). The variation of n-3 PUFA detected in the different studied organs of P. annectens ( Figure 6) was to some extent within the range found in other fish species (Suriah et al, 1995).…”
Section: Resultsmentioning
confidence: 61%
“…These parts may contribute to the total level of fatty acids, thus increasing the nutritional value of the fish. However, little is known about the fatty acids composition and profiles (%) of the Nile fishes (Elagba and Al-Sabahi, 2011) compared to other freshwater fishes (Ahlgren et al, 1994;Suriah et al, 1995;Zenebe et al, 1998;Bieniarz et al, 2000;Ackman et al, 2002;Fawole et al, 2007;Sharma et al, 2009;Ugoala et al, 2009). The present study is a first approach to determine the fatty acid composition and profiles of the African lungfish Protopterus annectens.…”
Section: Introductionmentioning
confidence: 99%
“…Fish oils are considered as the best natural source of highly unsaturated fatty acids, especially acids with more than three ethylenic groups or double bonds (Gruger et al 1964). Studies have shown that fish lipids are rich in PUFAs, especially the EPA and DHA from n-3 PUFAs bonds (Ugoala et al 2009, Sharma et al 2010. Fish have a high capacity for the transformation of C18 essential fatty acids (EFAs); C18:3 n-3 and C18:2 n-6 to C20:5 n-3, C22:6 n-3 and C20:4 n-6 and therefore, they may be an available source of such fatty acids to consumers (Henderson and Tocher 1987).…”
Section: Introductionmentioning
confidence: 99%